The EMPIRICAL STUDY: HOW FINANCIAL BEHAVIOR AND FOMO TO INFLUENCE GEN Z'S INVESTMENT DECISIONS WITH RISK TOLERANCE AS MODERATING VARIABLE - Monica Dewi (Fakultas Ekonomi, Universitas Negeri Jakarta, 2026)
This study aims to examine how financial behavior and Fear of Missing Out (FOMO) influence Generation Z’s investment decisions, with risk tolerance as a moderating variable. The research addresses the increasing participation of Gen Z in investment, often driven by emotional and social trends despite gaps in financial literacy. Using a quantitative method, data were collected through purposive and convenience sampling from 200 Gen Z individuals (aged 18–27) in Jakarta earning at least IDR 5,000,000 monthly. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was employed for analysis. The results indicate that financial literacy, financial inclusion, financial well-being, and FOMO significantly influence risk tolerance. Furthermore, financial literacy, inclusion, and well-being directly and indirectly affect investment decisions through risk tolerance. FOMO, while not directly significant, shows an indirect impact via increased risk tolerance. The findings conclude that risk tolerance plays a critical mediating role in shaping Gen Z’s investment decisions. These insights imply the need for targeted financial education programs that not only enhance financial knowledge but also address behavioral biases and emotional drivers, thereby enabling more rational and informed investment decisions among young investors.